Palynological characterization of species from the families Cactaceae and Melastomataceae: Caracterização palinológica de espécies das famílias Cactaceae e Melastomataceae - Aliny Wessler Karger; Denise M. D. da S. MOUGA (Acta Biológica Catarinense, 2025)
Pollen grains can be classified by the ir morphological characteristics such as the number of openings, ornamentation, size and structure of the exine. Aiming to contribute to the palynological characterization of the Cactaceae and Melastomataceae families, the pollen morphology of two Melastomataceae species was analyzed – Medinilla speciosa Blume and Pleroma candolleanum (Mart. ex DC.) –, and three Cactaceae species – Gymnocalycium anisitsii (K.Schum.), Mammillaria polythele Mart. and Pilosocereus leucocephalus (Poselg.) Byles & G.D. Rowley. From field trips, unopened buds were collected, whose anthers were removed, macerated and acetolyzed, resulting in slides that were analyzed using light microscopy and SEM (scanning electron microscopy). The Melastomataceae pollen grains studied are in monads, small, tricolporate-tripseudocolpate, subtriangular, suboblate, microverrucate. The pollen grains of Cactaceae are in monads, medium-large, tricolpate (two parasyncolpate), circular, suboblate oblatospheroidal, perforated granulated and microverrucate. Keywords: morphology, Palynology, pollen.